Penerapan Model Context, Input, Process, Product (CIPP) dalam Evaluasi Program Pendidikan Madrasah - Wahyudin, Aji (Transformation of Islamic Management and Education, 2025)
This study aims to evaluate the educational programs at private MTs (Islamic junior high schools) in Kediri Regency using the CIPP model (Context, Input, Process, Product). The evaluation was conducted to assess the extent to which the implemented programs align with the expected standards and their impact on the quality of learning in the two madrasahs. This research employed a qualitative approach with data collected through interviews, observations, and documentation. The findings reveal that most madrasahs have visions and missions aligned with the goals of national education; however, the main challenges lie in the limited resources, both in terms of teacher competencies and learning facilities. The curriculum applied tends to emphasize theoretical aspects while giving less attention to the development of practical skills such as communication, collaboration, and problem-solving. The teaching and learning process in most madrasahs is still dominated by lecture and memorization methods, with minimal use of technology and limited active interaction between teachers and students. Program evaluation has not been carried out systematically, with only a few madrasahs implementing data-based evaluations. The final results indicate that although students are able to achieve satisfactory academic scores, they still lack practical skills relevant to future needs. This study recommends enhancing teacher training, strengthening data-based evaluation, adjusting the curriculum to balance theory and practice, and utilizing technology in the learning process to improve the quality of education in madrasahs.